Chronic calcifying pancreatitis. Cephalic duodenopancreatectomy - Delgado Pereira, Bolívar (Cirugía del Uruguay, 2020)
A report is made of a typical case of calcifying chronic pancreatitis in an alcoholic, involving sharp pain and common duct occlusion. Resection ( cephaic duodeno-pancreatectomy) resulted in clinical remission, there remaining as sequela a shight exocrine and endocrine insufficienc'.